Alcoholic Hepatitis and COVID-19: The Question of Steroids. Issue 12 (7th December 2020) - Zelman, Sara; Holzwanger, Erik; Malik, Raza; Dickstein, Aaron
ABSTRACT: Severe acute respiratory syndrome coronavirus 2/novel coronavirus-19 (COVID-19) has rapidly become a global pandemic since the first cases from Wuhan, China, were reported in December 2019. The pandemic has made it more challenging to treat various gastrointestinal disorders, including acute alcoholic hepatitis (AH). One of the mainstays of treatment for severe AH involves corticosteroids (mainly prednisolone). A concern when treating with prednisolone is the worsening of underlying infection. There may be an additional risk in treating COVID-19–infected patients. We present a case of a patient with severe acute AH and concomitant COVID-19 infection who did well with corticosteroid therapy without evidence for worsening infection.